2000
DOI: 10.1016/s0022-2275(20)32401-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain acyl-CoA esters and acyl-CoA binding protein are present in the nucleus of rat liver cells

Abstract: A detailed analysis of the subcellular distribution of acyl-CoA esters in rat liver revealed that significant amounts of long-chain acyl-CoA esters are present in highly purified nuclei. No contamination of microsomal or mitochondrial marker enzymes was detectable in the nuclear fraction. C16:1 and C18:3-CoA esters were the most abundant species, and thus, the composition of acyl-CoA esters in the nuclear fraction deviates notably from the overall composition of acyl-CoA esters in the cell. After intravenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…5 C), which seemingly corresponded to its distribution in the ER and cytoplasmic LDs (Wilfling et al, 2013). Together with the nuclear presence of diacylglycerol and acyl-CoA (Elholm et al, 2000;Irvine, 2003), which are substrates of DGAT2, this result indicated that triglycerides could be synthesized in the nucleus. Furthermore, CCTα, the penultimate enzyme of the phosphatidylcholine synthetic Kennedy pathway that was reported to exist in cytoplasmic LDs (Krahmer et al, 2011), was also found around nuclear LDs (Figs.…”
Section: Lds Grow Inside the Nucleusmentioning
confidence: 72%
“…5 C), which seemingly corresponded to its distribution in the ER and cytoplasmic LDs (Wilfling et al, 2013). Together with the nuclear presence of diacylglycerol and acyl-CoA (Elholm et al, 2000;Irvine, 2003), which are substrates of DGAT2, this result indicated that triglycerides could be synthesized in the nucleus. Furthermore, CCTα, the penultimate enzyme of the phosphatidylcholine synthetic Kennedy pathway that was reported to exist in cytoplasmic LDs (Krahmer et al, 2011), was also found around nuclear LDs (Figs.…”
Section: Lds Grow Inside the Nucleusmentioning
confidence: 72%
“…In summary, the results presented herein for the first time demonstrated that LCFA-CoA, as well as LCFA, is localized in the nucleoplasm and nuclear membrane of living cells. Thus, earlier suggestions regarding the presence of LCFA-CoAs (68) and unesterified LCFA in nuclei (isolated by subcellular fractionation) were not simply due to artifacts of nuclear isolation or hydrolytic cleavage of esterified lipids to release LCFAs (64,79,80). The 23-30% colocalization of L-FABP and PPARR as well as L-FABP-mediated enhancement of LCFA-CoA as well as LCFA targeting to nuclei, especially nucleoplasm, suggested that L-FABP may serve to shuttle LCFAs and LCFA-CoAs to and/or into the nucleus for donating the ligands to PPARR.…”
Section: Discussionmentioning
confidence: 85%
“…A priori, it is not possible to directly compare the distribution of BODIPY-C16-S-S-CoA with that of naturally occurring metabolizable LCFA-CoAs in living cells. To date, the only comparisons that can be made are with purified rat liver nuclei, whose LCFA-CoA content was 0.32 nmol/g wet weight (68). It was reported that the total LCFA-CoA concentration of rat liver cells ranges from 15 to 83 nmol/g wet weight (reviewed in refs 67 and 69).…”
Section: Discussionmentioning
confidence: 99%
“…nLD could thus be involved in nuclear-lipid homeostasis and serve as an endonuclear buffering system that can rapidly provide or incorporate lipids involved in these processes. The ultimate role of the nLD lipids could be the regulation of enzymes involved in nuclear-lipid metabolism, signaling events, and/or interactions with transcription factors such as the PPAR and the HNF 4 α that have FA as ligands [51]. Moreover, when these processes are shut down and the bound lipids (e.g., the FA, DG, phosphoinositides) are accordingly released from the specific active site and/or receptor, these lipidic regulatory ligands could become incorporated into nLD.…”
Section: Discussionmentioning
confidence: 99%